Markers of perinatal hypoxia–ischaemia and neurological injury: assessing the impact of insult duration. (23rd December 2019) - Baxter, Peter
Abstract : Hypoxic–ischaemic insults occurring during or after birth can cause both acute and long‐term neurological impairment. The duration of the insult is a critical factor, but most published reports of duration have important limitations. After the onset of a persistent bradycardia in 125 term born infants, abnormal outcomes occurred in two by 10 minutes, in 12 out of 47 (26%) delivered between 11 and 20 minutes, and in 55 out of 65 (85%) delivered after 20 minutes. Series with unspecified gestation or including infants born preterm give comparable results in over 500 additional cases. Before 20 minutes there was little correlation with severity, while after 20 minutes most were severely impaired. Limited neuroimaging data suggest that damage restricted to the basal ganglia and thalamus may begin to occur after 10 minutes, associated Rolandic damage after 15 minutes, and other cortical involvement after 20 minutes. Associated white matter damage can occur after any duration. There were little data for other patterns of damage. What this paper adds: Some term born infants can withstand 20 minutes of fetal bradycardia without acute or chronic damage. Durations in humans are not the same as in animal models. What this paper adds: Some term born infants can withstand 20 minutes of fetal bradycardia without acute or chronic damage. Durations in humans are not the same as in animal models. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Fahey on pages 539–540 of this issue. Resumen: Marcadores de hipoxia‐isquemia perinatal y daño neurológico: evaluación del impacto de la duración del insulto: Los insultos hipóxico‐isquémicos que ocurren durante o después del parto pueden causar un daño neurológico agudo y también a largo plazo. La duración del insulto es un factor crítico, pero la mayoría de los estudios publicados tienen limitaciones importantes. Después del inicio de un evento centinela y/o bradicardia persistente en 132 recién nacidos a término, se encontraron resultados anormales en dos nacidos en menos de 10 minutos, en 14 de 60 (23%) nacidos entre 10 y 20 minutos, y en 60 de 70 (86%) nacidos después de 20 minutos. Las series con edad gestacional no especificada o que incluyen recién nacidos prematuros tienen resultados comparables en más de 500 casos adicionales. Antes de los 20 minutos hubo poca correlación con la severidad, mientras que después de 20 minutos la mayoría quedaron gravemente deteriorados. Datos limitados de neuroimagenes sugieren que el daño restringido a los ganglios basales y el tálamo puede comenzar a ocurrir después de 10 minutos, el daño rolandico asociado después de 15 minutos y otra afectación cortical después de 20 minutos. El daño asociado a la materia blanca puede ocurrir después de cualquier duración. No hubo datos de otros patrones de daño. Resumo: Marcadores de hipóxia‐isquemia perinatais e lesão neurológica: avaliando o impacto da duração do insulto: Insultos hipóxico‐isquêmicos que ocorrem durante ou após o nascimento podem causar danos neurológicos agudos e de longo prazo. A duração do insulto é um fator crítico, mas a maior parte dos relatos pubicados sobre a duração tem limitações importantes. Após o início de um evento sentinela e/ou bradicardia persistente em 132 lactentes a termo, resultados anormais ocorreram em 2 em menos de 10 minutos, em 40 de 60 (23%) entre 10 e 20 minutos, e em 60 de 70 (86%) após 20 minutos. Séries com gestação não especificada ou incluindo lactentes nascidos prematuros deram resultados comparáveis em cerca de 500 casos adicionais. Antes de 20 minutos houve pouca correlação com a severidade, e após 20 minutos a maior parte teve comprometimento severo. Dados limitados de neuroimagem sugerem que o dano restrito aos gânglios da base e tálamo podem ocorrer após 10 minutos, dano Rolândico associado após 15 minutos, e outro envolvimento cortical após 20 minutos. Dano associado da substância branca pode ocorrer com qualquer duração. Não há dados para outros padrões de danos.